Editorial - Fernández-Arata, Manuel (2017)
The editing of scientific journals is a process which is marked by high demands and utmost competitiveness, as evidenced by the rising rejection rates of the manuscripts submitted to arbitration. Today, more than ever, the scientific community has a very strong perception of the journals as the main platform for dissemination and exchange of original, accurate and honest information. That is why the publishing activity is carried out by a cohesive team; first of all, the associate editors are the first ones to assess the quality and originality of the manuscripts and, if approved, they are submitted in such a way that the compliance with the established international standards can be guaranteed; secondly, the scientific committee participates as the last specialized filter which, under the double-blind peer review system, ensures the objectivity in the evaluation process of the manuscripts, so that they are a contribution to new insights for the advancement of our science. DOI: https://doi.org/10.24265/liberabit.2017.v23n1.11